Vom „Wächter am Tor“ zum „einsamen Wolf“. Der Multifunktionär Hans-Michael Fiedler und die Transformation der radikalen Rechten in Südniedersachsen - Trittel, Katharina 1984- (Universitätsverlag Göttingen, 2022)
Since 2019, the Research and Documentation Center for the Analysis of Political and Religious Extremisms in Lower Saxony (FoDEx) has been managing the estate of the right-wing extremist multifunctionalist Hans-Michael Fiedler. The processing and evaluation of the legacy makes it possible to make previously untapped sources accessible to research and the (specialist) public. The indexing of the material opens up new perspectives on a central actor of the radical right in Germany as well as its networks in order to better understand the political structures of right-wing radicalism in the long term. This study presents initial results by first focusing on Fiedler's political biographical development from the perspective of actor-centered right-wing extremism research. Using this radical right actor as an example, it analyzes the genesis of the radical right in southern Lower Saxony from the 1960s to the early 1990s. Translated with www.DeepL.com/Translator (free version)